Wind turbine wake detection with a single Doppler wind lidar. (June 2015) - Wang, H; Barthelmie, R J
Abstract: Using scanning lidar wind turbine wakes can be probed in three dimensions to produce a wealth of temporally and spatially irregular data that can be used to characterize the wakes. Unlike data from a meteorological mast or upward pointing lidar, the spatial coordinates of the measurements are not fixed and the location of the wake also varies in three dimensions. Therefore the challenge is to provide automated detection algorithms to identify wakes and quantify wake characteristics from this type of dataset. Here an algorithm is developed and evaluated on data from a large wind farm in the Midwest. A scanning coherent Doppler wind lidar was configured to measure wind speed in the wake of a continuously yawing wind turbine for two days during the experiment and wake profiles were retrieved with input of wind direction information from the nearby meteorological mast. Additional challenges to the analysis include incomplete coverage of the entire wake due to the limited scanning domain, and large wind shear that can contaminate the wake estimate because of the height variation along the line-of-sight. However, the algorithm developed in this paper is able to automatically capture wakes in lidar data from Plan Position Indicator (PPI) scans and the resultant wake statistics are consistent with previous experiment's results.